Stress-augmented thermal activation: Tribology feels the force - Spikes,HA (Friction, 2018)
In stress-augmented thermal activation, the activation energy barrier that controls the rate of atomic and molecular processes is reduced by the application of stress, with the result that the rate of these processes increases exponentially with applied stress. This concept has particular relevance to Tribology, and since its development in the early twentieth century, it has been applied to develop important models of plastic flow, sliding friction, rheology, wear, and tribochemistry. This paper reviews the development of stress-augmented thermal activation and its application to all of these areas of Tribology. The strengths and limitations of the approach are then discussed and future directions considered. From the scientific point of view, the concept of stress-augmented thermal activation is important since it enables the development of models that describe macroscale tribological performance, such as friction coefficient or tribofilm formation, in terms of the structure and behaviour of individual atoms and molecules. This both helps us understand these processes at a fundamental level and also provides tools for the informed design of lubricants and surfaces.